Pola Makan dan Obesitas berhubungan dengan Riwayat Kejadian Hipertensi di Puskesmas Rawasari - Filius Chandra; Iswanto Iswanto; Aisah Aisah (Jurnal Akademika Baiturrahim Jambi, 2021)
Hypertension is a non-communicable disease (PTM) which is a very serious health problem both in the world and in Indonesia. One sign of hypertension is an increase in blood pressure. Hypertension is called the silent killer, because people with hypertension often show no symptoms. The research objective was to determine the relationship between diet and obesity with the incidence of hypertension at the Rawasari Public Health Center in Jambi City in 2019.This study used a cross sectional design, which was carried out in August 2019, 64 hypertension respondents at the Rawasari Health Center were taken using purposive sampling technique. The research variables were diet and obesity  which were analyzed using the chi-square test.This study showed that most respondents had hypertension (92.2%). most of the diet frequently (51.6%). and  nutritional status (50%). Chi-square analysis showed  that there was a relationship between diet and hypertension (p= 0.016) and chi-square analysis showed that there was no relationship between obesity  and hypertension (p= 0.0162). There is no significant relationship between diet and hypertension, and there is no significant relationship between nutritional status and hypertension